A Comprehensive Systematic Review of The Relationship Between Excessive Analgesic Use and Migraine Chronicity - Achmad Deddy Fatoni; An Nur Rahmad Nugroho (The Indonesian Journal of General Medicine, 2026)
Introduction: Medication overuse headache (MOH) is a significant complication in migraine management, where excessive use of acute analgesics paradoxically leads to increased headache frequency and chronicity. Understanding the bidirectional relationship between analgesic overuse and the transformation from episodic to chronic migraine (CM) is crucial for developing effective treatment strategies. This systematic review synthesizes evidence on this relationship and evaluates the efficacy of various interventions. Methods: A systematic methodology was employed to screen and extract data from 80 relevant studies. Inclusion criteria focused on adult migraine populations, clear definitions of analgesic overuse and migraine chronicity, quantitative outcome data, and studies with adequate sample sizes. Data extraction covered study design, definitions of key constructs, population characteristics, evidence of the analgesic-overuse-chronicity relationship, effects of interventions, and moderating factors. Results: Analgesic overuse is highly prevalent (40-78%) in CM populations, with triptans, combination analgesics, and NSAIDs being most commonly overused. Evidence strongly supports a causal relationship from overuse to chronicity, demonstrated by significant improvements following medication withdrawal. Detoxification combined with preventive treatment achieved the highest success rates (up to 96.8% MOH cure). Anti-CGRP monoclonal antibodies (erenumab, fremanezumab, galcanezumab, eptinezumab) showed consistent efficacy in reducing both migraine days and acute medication use, with 55-61% of patients reverting from overuse without formal detoxification. OnabotulinumtoxinA, gepants (e.g., atogepant), topiramate, and behavioral interventions (mindfulness, CBT) also demonstrated significant benefits. Outcomes varied by medication type overused, with triptan overuse associated with better prognosis, and were moderated by patient factors such as psychological comorbidities and pain catastrophizing. Discussion: The findings highlight a complex, bidirectional relationship where overuse perpetuates chronicity through mechanisms like central sensitization and altered pharmacokinetics, while effective preventive treatment reduces the need for acute medication. The evidence supports stratified treatment approaches: combined withdrawal and prevention for amenable patients, anti-CGRP therapies for those intolerant to withdrawal or with prior treatment failures, and integrated behavioral-pharmacological strategies for those with psychological comorbidities. Conclusion: Excessive analgesic use is a key modifiable risk factor in migraine chronicity. A multimodal, patient-centered approach is essential, prioritizing medication withdrawal where feasible, leveraging the efficacy of newer preventive therapies like anti-CGRP agents, and addressing psychological moderators. Future research should focus on long-term outcomes, personalized medicine based on overuse medication type, and the neurobiological mechanisms underlying the overuse-chronicity cycle.